Future changes in the seasonal habitat suitability for anchovy (Engraulis japonicus) in Korean waters projected by a maximum entropy model - Bang, Minkyoung; Sohn, Dongwha; Kim, Jung Jin; Choi, Wonkeun; Jang, Chan Joo; Kim, Changsin (Frontiers in Marine Science, 2022)
Anchovy (Engraulis japonicus), a commercially and biologically important fish species in Korean waters, are small pelagic fish that are sensitive to environmental change. Future changes in their distribution in Korean waters with significant environmental change, remain poorly understood. In this study, we examined the projected changes in the seasonal habitat of anchovy in Korean waters in the 2050s under three future climate change scenarios (RCP 2.6, RCP 4.5, and RCP 8.5) by using a maximum entropy model (MaxEnt). The seasonal MaxEnts were constructed by monthly anchovy presence points and five environmental variables (sea surface temperature, sea surface salinity, sea surface current speed, mixed layer depth, and chlorophyll-a concentration) from 2000–2015. Future changes in the anchovy habitat in Korean waters showed variation with seasonality: in the 2050s, during winter and spring, the future anchovy habitat are projected to increase by 19.4–38.4%, while in summer and fall, the habitat area is projected to decrease by up to 19.4% compared with the historical period (2000–2015) under the three different RCPs. A substantial decline (16.5–60.8%) is expected in summer in the East China Sea and the Yellow Sea—their main spawning habitats. This considerable decrease in the spawning habitat may contribute to a decrease in the anchovy biomass in Korean waters, relocation of the spawning area, and changes in the timing of their reproduction. Our findings suggest that seasonal variation of the anchovy habitat should be considered to ensure the effective planning of future management strategies for the effect of climate change on fisheries resources, particularly for environmentally sensitive species, such as anchovy.